Portraying infective endocarditis: results of multinational ID-IRI study - Erdem, Hakan; Puca, Edmond; Ruch, Yvon; Santos, Lurdes; Ghanem-Zoubi, Nesrin; Argemi, Xavier; Agalar, Canan (Springer, 2019)
Infective endocarditis is a growing problem with many shifts due to ever-increasing comorbid illnesses, invasive procedures, and increase in the elderly. We performed this multinational study to depict definite infective endocarditis. Adult patients with definite endocarditis hospitalized between January 1, 2015, and October 1, 2018, were included from 41 hospitals in 13 countries. We included microbiological features, types and severity of the disease, complications, but excluded therapeutic parameters. A total of 867 patients were included. A total of 631 (72.8%) patients had native valve endocarditis (NVE), 214 (24.7%) patients had prosthetic valve endocarditis (PVE), 21 (2.4%) patients had pacemaker lead endocarditis, and 1 patient had catheter port endocarditis. Eighteen percent of NVE patients were hospital-acquired. PVE patients were classified as early-onset in 24.9%. A total of 385 (44.4%) patients had major embolic events, most frequently to the brain (n = 227, 26.3%). Blood cultures yielded pathogens in 766 (88.4%). In 101 (11.6%) patients, blood cultures were negative. Molecular testing of vegetations disclosed pathogens in 65 cases. Overall, 795 (91.7%) endocarditis patients had any identified pathogen. Leading pathogens (Staphylococcus aureus (n = 267, 33.6%), Streptococcus viridans (n = 149, 18.7%), enterococci (n = 128, 16.1%), coagulase-negative staphylococci (n = 92, 11.6%)) displayed substantial resistance profiles. A total of 132 (15.2%) patients had cardiac abscesses; 693 (79.9%) patients had left-sided endocarditis. Aortic (n = 394, 45.4%) and mitral valves (n = 369, 42.5%) were most frequently involved. Mortality was more common in PVE than NVE (NVE (n = 101, 16%), PVE (n = 49, 22.9%), p = 0.042).
Keywords: Infective endocarditis; Prosthetic; Native; S; aureus; Blood culture